2010
DOI: 10.1677/erc-10-0032
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β and the progression of prostate cancer: role of 5α-androstane-3β,17β-diol

Abstract: Prostate cancer (PC) develops in response to an abnormal activation of androgen receptor induced by circulating androgens and, in its initial stages, is pharmacologically controlled by androgen blockade. However, androgen ablation therapy often allows androgen-independent PC development, generally characterized by increased invasiveness. We previously reported that 5a-androstane-3b,17b-diol (3b-Adiol) inhibits the migration of PC cell lines via the estrogen receptor b (ERb) activation. Here, by combining in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 48 publications
(59 reference statements)
5
26
0
Order By: Relevance
“…Of interest, recruitment of ER␤/eNOS also was abrogated by the addition of the androgen metabolite 3␤-adiol, a natural ER␤ ligand, whereas no effect was obtained with the more potent natural agonist E 2 or the antagonist of ER action, 4-hydroxitamoxifen (data not shown). In this regard, our results are in agreement with those of Dondi et al (32), who demonstrated that ER␤ activated by 3␤-adiol, but not by E 2 , exerts antiproliferative and antiinvasion effects in the PC3 cell line and in xenografts in vivo. We expanded on this aspect and analyzed by confocal microscopy the nuclear/cytoplasmic distribution of ER␤ and eNOS in cells untreated or treated with ICI or 3␤-adiol.…”
Section: Fig 5 In Vivo Chip Assays a In Vivosupporting
confidence: 93%
See 2 more Smart Citations
“…Of interest, recruitment of ER␤/eNOS also was abrogated by the addition of the androgen metabolite 3␤-adiol, a natural ER␤ ligand, whereas no effect was obtained with the more potent natural agonist E 2 or the antagonist of ER action, 4-hydroxitamoxifen (data not shown). In this regard, our results are in agreement with those of Dondi et al (32), who demonstrated that ER␤ activated by 3␤-adiol, but not by E 2 , exerts antiproliferative and antiinvasion effects in the PC3 cell line and in xenografts in vivo. We expanded on this aspect and analyzed by confocal microscopy the nuclear/cytoplasmic distribution of ER␤ and eNOS in cells untreated or treated with ICI or 3␤-adiol.…”
Section: Fig 5 In Vivo Chip Assays a In Vivosupporting
confidence: 93%
“…In addition, recent data indicate that ER␤ is highly sensitive to variations in the prostate microenvironment (10,(32)(33)(34)(35) and particularly affected by the relative abundance of its natural ligand 5␣-androstane-3␤,17␤-diol (36,37). Therefore, we asked whether 3␤-adiol-activated ER␤ would contribute to the rescue of GSTP1 expression and to the reversion of the aggressive phenotype.…”
Section: Effects Of 5␣-androstane-3␤17␤-diol (3␤-adiol) On Gstp1 Expmentioning
confidence: 99%
See 1 more Smart Citation
“…The inactive androgen, testosterone, is either reduced to the active form DHT or aromatized to 17b-oestradiol (E 2 ); DHT and E 2 bind androgen receptor (AR) and oestrogen receptor (ER)s respectively, with different and sometime opposing effects on the prostate target cells (Bilińska et al 2006, Carruba 2007, Ellem & Risbridger 2010. Furthermore, DHT can also be reduced to 5a-androstane-3b,17b-diol (3b-Adiol), a metabolite which binds and activate preferentially the ERb isoform (Imamov et al 2004, Guerini et al 2005, but not AR, counteracting DHT action on the growth of the normal prostate (Weihua et al 2002) and on the proliferation, migration and metastasis of prostate cancer cells (Weihua et al 2002, Dondi et al 2010. When and how perturbation of this complex hormone balance occurs during prostate tumourigenesis is not easy to address experimentally.…”
Section: Molecular Imaging Of Hormone Productionmentioning
confidence: 99%
“…In some target cell, including endocrine-related tumour cells, the activated receptor is able to stimulate G1/S-phase transition through the G1 restriction point by inducing the expression of specific cell cycle regulators, such as c-myc, c-fos, c-jun and cyclinD1 (Butt et al 2005, Lamont & Tindall 2010. Stimulation of these mitogenic pathways eventually promotes the hyperplastic growth of epithelial cells in reproductive tissues; however, this proliferative induction does not entail for the full carcinogenic potential of a dysregulated steroid hormone signal: indeed, steroid hormones modulate apoptosis, promote migration, metastasis and angiogenesis functions in tumour cells (Kaarbø et al 2007, Lewis-Wambi & Jordan 2009, Sarker et al 2009, Dondi et al 2010. Current hypothesis propose that the influence of hormones extends throughout the carcinogenesis process.…”
Section: Introductionmentioning
confidence: 99%